O genocídio da população negra como política de Estado: estudo de caso da chacina do Jacarezinho - Pereira, Vanderson dos Santos (2023)
The policy of segregation and extermination of the black population has been adopted by Brazil since the colony, with racism being one of the main constituent elements of the Brazilian social structure. The methods of making black bodies die were only modernized and institutionalized, with the Criminal Policy representing, today, the most effective way of depositing in the black, poor and marginalized, the justifications for their annihilation. The police is not the only instrument used by the State to achieve its punitive power, but, alongside the prison, it is one of the most efficient and aggressive. This is what the data reveals, with the murder of black people representing 80% of deaths in police operations in 2019 and black people being 2.6 times more likely to be murdered than white people. In May 2021, the State once again took its policy of killing a poor community, under the justification of combating crime. He entered the Jacarezinho favela, in Rio de Janeiro, and killed 28 people, leading to the biggest massacre ever carried out in that city. It was because of these facts that this research was designed, with the general objective of analyzing police lethality against the black population in Brazil, using the Jacarezinho massacre as a reference, which was done through the case study strategy. For that, specifically, we sought to discuss criminal policy in Brazil from criminological concepts, through the theoretical framework of critical criminology. Then, through bibliographical and documentary research, police lethality in Brazil was discussed from a racial perspective. And finally, seeking to achieve the proposed general objective, it was debated, as a case study, the police slaughter committed in the Jacarezinho favela. With that, considering the need for a change in the structure of Brazilian society, especially in public security policies, this research sought to expose the relationship between police lethality, as an instrument of state policy, and the racial issue. And he was able to verify, in the course of the discussion, that the violence perpetrated by the State through police institutions is the result of a governability supported by racist biases, with the black, poor and peripheral, considered subject subject to the violent control of the State, without the consideration of the basic norms for the protection of human rights inherent to any citizen.